Firm entry and labor market dynamics - Enchuan Shao; Pedro Silos (Federal Reserve Bank of Atlanta, 2008)
We present a model of aggregate fluctuations in which monopolistic firms face sunk costs to enter the production process and labor markets are characterized by search and matching frictions. Entrants post vacancies and are matched to idle workers. Our specification of sunk costs gives rise to a countercyclical net present value of a vacancy; it is always zero in models where entry is free. The model displays a strong degree of amplification and propagation. The time-varying value of a vacancy has implications for the surplus division between firms and workers over business cycle. In the data, we proxy this division using the ratio of corporate profits to output and workers' compensation to output. We document the cyclical behavior of profit's and labor's shares: Profit's share leads the cycle and is procyclical and more volatile than output. Labor's share inversely leads the cycle and is weakly countercyclical and smoother than output. Our model is consistent with the cross-correlations of both shares and the higher volatility of the share of profits. Regarding propagation and amplification, the model matches the persistence of vacancy creation and two-thirds of the observed volatility of market tightness relative to output.
Keywords: E24; E32; J32; 330; search; matching; business cycles; income shares